2023
DOI: 10.3389/fpls.2023.1137299
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptome and metabolome analysis revealed that flavonoids enhanced the resistance of Oryza sativa against Meloidogyne graminicola

Abstract: Rice is a crucial food crop worldwide, but its yield and quality are significantly affected by Meloidogyne graminicola is a root knot nematode. No rice variety is entirely immune to this nematode disease in agricultural production. Thus, the fundamental strategy to combat this disease is to utilize rice resistance genes. In this study, we conducted transcriptome and metabolome analyses on two rice varieties, ZH11 and IR64. The results indicated that ZH11 showed stronger resistance than IR64. Transcriptome anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Plants are well known to respond to pathogens through the activation of the phenylpropanoid pathway, leading to the biosynthesis of flavonoids, isoflavonoids, and phenolics [ 2 , 31 , 33 , 34 ]. The combined transcriptome and metabolome analysis showed that DEGs and DAMs involved in flavonoid biosynthesis pathways were significantly enriched (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants are well known to respond to pathogens through the activation of the phenylpropanoid pathway, leading to the biosynthesis of flavonoids, isoflavonoids, and phenolics [ 2 , 31 , 33 , 34 ]. The combined transcriptome and metabolome analysis showed that DEGs and DAMs involved in flavonoid biosynthesis pathways were significantly enriched (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…capsici . The crucial role of the activation of flavonoid biosynthesis pathways in response to pathogens has been reported in cucumber [ 31 ], Zanthoxylum bungeanum [ 33 ], and rice [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation